Handbook of self assembled semiconductor nanostructures for novel devices in photonics and electronics - Henini, Mohamed (Elsevier, 2008)
The self-assembled nanostructured materials described in this book offer a number of advantages over conventional material technologies in a wide range of sectors. World leaders in the field of self-organisation of nanostructures review the current status of research and development in the field, and give an account of the formation, properties, and self-organisation of semiconductor nanostructures. Chapters on structural, electronic and optical properties, and devices based on self-organised nanostructures are also included. Future research work on self-assembled nanostructures will connect diverse areas of material science, physics, chemistry, electronics and optoelectronics. This book will provide an excellent starting point for workers entering the field and a useful reference to the nanostructured materials research community. It will be useful to any scientist who is involved in nanotechnology and those wishing to gain a view of what is possible with modern fabrication technology. Mohamed Henini is a Professor of Applied Physics at the University of Nottingham. He has authored and co-authored over 750 papers in international journals and conference proceedings and is the founder of two international conferences. He is the Editor-in-Chief of Microelectronics Journal and has edited three previous Elsevier books. Key Features: - Contributors are world leaders in the field - Brings together all the factors which are essential in self-organisation of quantum nanostructures - Reviews the current status of research and development in self-organised nanostructured materials - Provides a ready source of information on a wide range of topics - Useful to any scientist who is involved in nanotechnology - Excellent starting point for workers entering the field - Serves as an excellent reference manual.
Keywords: Nanostructured materials.; Semiconductors.; Photonics.; elektronické knihy; electronic books